The Ministry of cantors - Harmon, Kathleen A., 1944-- (Collegeville, Minnesota : Liturgical Press, 2016)
The Ministry of Cantors has long been a valuable resource for music ministry formation. This new edition includes valuable insights from Sing to the Lord: Music in Divine Worship. It addresses more fully the distinction between the roles of psalmist and cantor, suggests further concrete ways a paschal mystery spirituality must undergird both roles, and offers practical insights for helping one discern the call to be a cantor. New content also explores the power of the psalms to transform those singing into the kind of persons God is calling them to be.
The cantor and the paschal mystery
Includes bibliographical references
Keywords: Catholic Church -- Liturgy -- Study and teaching; Church music -- Catholic Church -- Instruction and study; Ministers of music